THE ACQUISITION OF PRAGMATIC DIMENSION IN THE TEACHING AND LEARNING OF MALAY: AN EARLY REVIEW - Wahid, Lokman Abd (Jurnal Pendidikan Bahasa dan Sastra, 2015)
AbstractThis study is focussing on the acquisition of pragmatic structure in the first language parameter, particularly in Malay.  The pragmatic structure assumes that a speaker innately has a choice for Face Threatening Acts (FTA's) in his construction of sentences for a particular conversation. The structure of FTA’s are Bald On-Record (BOR), Negative Politeness (NP), Positive Politeness (PP), and Off-Record-indirect strategy (OR).  From the pragmatic perspective, each of the FTA’s consists of a certain purpose. To look at the competency of pragmatic acquisition structure, subjects of this study were exposed through classroom interactions based on three learning outcomes.   For each learning outcome, subjects were given six situations which totalling to 18 situations for all the three learning outcomes mentioned.  Each situations demands subjects to discuss and interact using the FTA’s that they have already acquired.  The study shows that in regard of the acquisition of FTA’s among subjects, BOR acquired the highest score, followed by PP, NP, and OR in all the six situations undergone by the subjects.  Keywords: Face Threatening Acts (FTA’s), language acquisition, pragmatic AbstrakPenelitian ini berfokus pada akuisisi struktur pragmatis dalam parameter bahasa pertama, terutama dalam bahasa Melayu. Struktur pragmatis berasumsi bahwa seorang penutur memiliki pilihan untuk Tindak Tutur yang Mengancam Muka (Face Threatening Acts/FTA) dalam konstruksi kalimatnya dalam percakapan tertentu. Struktur FTA adalah Bald On-Record (BOR), Kesopanan Negatif (Negative Politeness/NP), Kesopanan Positif  (Positive Politeness/PP), dan strategi tidak langsung Off-Record (OR). Dari perspektif pragmatis, masing-masing dari FTA mengandung tujuan tertentu. Untuk melihat kompetensi akuisisi struktur pragmatis, subyek penelitian ini mengikuti interaksi kelas berdasarkan tiga hasil belajar. Untuk setiap hasil belajar, mata pelajaran diberi enam situasi sebanyak 18 situasi untuk ketiga hasil belajar yang disebutkan. Setiap situasi menuntut subyek untuk membahas dan berinteraksi menggunakan FTA yang telah mereka peroleh. Penelitian ini menunjukkan bahwa dalam hal akuisisi FTA, BOR memperoleh skor tertinggi, diikuti oleh PP, NP, dan OR dalam semua enam situasi yang dialami oleh subyek.Kata kunci: Tindak tutur mengancam muka (FTA), penguasaan bahasa, pragmatis